2014
DOI: 10.1186/1475-9276-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Mental health inequalities in Slovenian 15-year-old adolescents explained by personal social position and family socioeconomic status

Abstract: IntroductionMental health inequalities are an increasingly important global problem. This study examined the association between mental health status and certain socioeconomic indicators (personal social position and the socioeconomic status of the family) in Slovenian 15-year-old adolescents.MethodsData originate from the WHO-Collaborative cross-national ‘Health Behavior in School-aged Children’ study conducted in Slovenia in 2010 (1,815 secondary school pupils, aged 15). Mental health status was measured by:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 34 publications
(45 reference statements)
9
29
0
4
Order By: Relevance
“…For family financial status, most studies have found that low family financial income is related to greater problem behaviours in both parents and children (Bask, ; Ma et al, ; Reiss, ). These results are also confirmed in other former Yugoslavia countries such as Bosnia and Herzegovina and Slovenia (Klanšček, Ziberna, Korošec, Zurc, & Albreht, ; Pranjić, Brković, & Beganlić, ). Ajduković and Rajhvajn Bulat () found that for externalising problems, both those adolescents who perceive their family as having low material status and those who perceive their family as having high material status have more problems than adolescents who believe that their families have the same amount of money as their peers' families.…”
Section: Discussionsupporting
confidence: 72%
“…For family financial status, most studies have found that low family financial income is related to greater problem behaviours in both parents and children (Bask, ; Ma et al, ; Reiss, ). These results are also confirmed in other former Yugoslavia countries such as Bosnia and Herzegovina and Slovenia (Klanšček, Ziberna, Korošec, Zurc, & Albreht, ; Pranjić, Brković, & Beganlić, ). Ajduković and Rajhvajn Bulat () found that for externalising problems, both those adolescents who perceive their family as having low material status and those who perceive their family as having high material status have more problems than adolescents who believe that their families have the same amount of money as their peers' families.…”
Section: Discussionsupporting
confidence: 72%
“…Since these shorter versions are practical to use and have a low administrative burden while maintaining many of the advantages of the KIDSCREEN-52 [10], they have been used in many countries for large-scale population-based studies [11,12], studies that investigate factors that impact the HRQOL of children with chronic diseases or conditions [13,14], and interventional [15] and longitudinal studies [16,17]. In particular, the use of these questionnaires for studies of HRQOL of children with mental health problems has increased [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…We investigated, in a sample of 112 unemployed parents of adolescents aged [10][11][12][13][14][15][16][17][18][19] years, the links between parental distress and change in youth emotional problems related to parental unemployment, and the moderation roles of parent-youth relationship and financial deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, adolescents are likely to become especially vulnerable to poorer well-being and more likely to develop mental health problems when their families are facing stress and socioeconomic deprivation (9-11). A recent study in Slovenia showed that adolescents who report living in socioeconomic deprivation exhibit lower life satisfaction and a poorer quality of life than those living in better socioeconomic conditions (12). Therefore, such adverse living situations constitute a serious threat that can undermine adolescents' development, well-being and future health outcomes in adult life (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation